Arthroscopic Treatment of Shoulder Instability with Glenoid Bone Loss Using Distal Tibia Allograft Augmentation. Issue 7 (21st July 2017) - Wong, Ivan; Amar, Eyal; Coady, Catherine M.; Smith, Ben; Glazebrook, Mark; Konstantinidis, George; Dillman, Daryl B.
Objectives: The purpose of this study was to retrospectively analyze prospectively collected data to present the clinical and radiological short term outcomes of patients who underwent anatomic glenoid reconstruction using distal tibia allograft to treat shoulder instability with glenoid bone loss. Methods: Over four years, 44 patients (31 patients were male and 13 female with mean age of 29.73 years) underwent arthroscopic stabilization with capsulelabral Bankart repair and allograft bony augmentation of the glenoid for recurrent shoulder instability with significant bone loss by the same surgeon. 14 patients were revision cases of previous surgery. Preoperative and postoperative functional assessment was performed with the Western Ontario Shoulder Instability Index (WOSI) questionnaire, and radiological assessment was performed with radiographs and CT scans. The Average follow-up was 2 years. Results: 97% (43/44) patients had no dislocations or subluxations at the most recent followup. The mean pre and postoperative WOSI scores were 40.54 and 72.65 respectively (p<0.001). No patients developed nerve injury. One patient presented with hardware failure at 3 years post-op. Two other patients had graft absorption and 6 patients had partial graft resorption but none had symptoms of instability. The mean postoperative active shoulder range of motion was forward flexion 170.1o, abduction 168.9o, internal rotation 69.5o and external rotation 57.5o. Grafts positioning was flush with the glenoid in 93% of cases, vertical positioning was excellent in 89% (35 o'clock). Conclusion: Arthroscopic stabilization of the shoulder with distal tibia allograft augmentation is a good safety profile technique with good results at average of two years follow up.